2016
DOI: 10.3390/coatings6010012
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Sol-Gel Coatings: Smart and Green Materials for Corrosion Mitigation

Abstract: Corrosion degradation of materials and metallic structures is one of the major issues that give rise to depreciation of assets, causing great financial outlays in their recovery and or prevention. Therefore, the development of active corrosion protection systems for metallic substrates is an issue of prime importance. The promising properties and wide application range of hybrid sol-gel-derived polymers have attracted significant attention over recent decades. The combination of organic polymers and inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 140 publications
2
70
0
2
Order By: Relevance
“…It was found that increasing the organic content (via the glyc id yl group of the GPTMS) in the sol-gel based matrix formulation helped to improve the adhesion of the coating to the substrate as well as provide more uniform and thicker coatings, which is in agreement with other studies [32,33]. Thus, a TES40/GPTMS molar ratio of 1:1.8 was selected as the preferred matrix formulation due to its uniformity, its lower susceptibility to cracking and its enhanced thickness.…”
Section: Coating Microstructuresupporting
confidence: 80%
“…It was found that increasing the organic content (via the glyc id yl group of the GPTMS) in the sol-gel based matrix formulation helped to improve the adhesion of the coating to the substrate as well as provide more uniform and thicker coatings, which is in agreement with other studies [32,33]. Thus, a TES40/GPTMS molar ratio of 1:1.8 was selected as the preferred matrix formulation due to its uniformity, its lower susceptibility to cracking and its enhanced thickness.…”
Section: Coating Microstructuresupporting
confidence: 80%
“…Therefore, future trends for commercial OWS coatings are predicted to match current research interests such as low cost, pollution-free, self-healing products that are easy to synthesize and apply. The coatings should be effective in corrosion control for long service lives in a wide range of environments [108]. It is clear that studies on the behaviour of innovative coating systems need to be performed in OWSs since scarce information was found by the authors of this paper.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…In the last few decades, several types of organic-based coatings have been developed [85], including anti-fouling paints [70,[86][87][88][89][90][91][92][93][94], composites and nano-coatings [94][95][96], self-healing coatings [97][98][99][100][101][102][103][104][105][106][107], and hybrid sol-gel materials [98,[108][109][110][111][112][113][114][115][116][117][118][119][120][121] among others. However, as far as the authors' knowledge, very few studies were performed on OWSs using self-healing and hybrid sol-gel coatings.…”
Section: Coating Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many new inhibitor systems have been the subject of extensive research, including rare earths [1][2][3][4][5][6][7][8][9][10][11][12][13][14], vanadates [15,16], organic compounds [17][18][19][20][21][22][23], sacrificial particles or functional properties in coatings [24][25][26][27][28], double-layered hydroxides containing inhibitors [29][30][31][32][33][34][35][36][37][38][39][40][41] and, in many cases, combinations of these. The search for alternatives is probably most intense for aerospace applications, where chromate inhibitors have been the mainstay of corrosion prevention for many decades.…”
Section: Introductionmentioning
confidence: 99%